Analysis of teaching satisfaction measured by the student in university contexts following the Educational Situation Quality Model - Abellán Roselló, Laura; Fernández Rodicio, Clara Isabel (Revista Complutense de Educación, 2023)
The Quality Model of the Educational Situation, hereafter MOCSE, is an instructional model that understands the teaching-learning process in which motivation is the central axis and satisfaction is at its last stage. The objective of the present study focuses on examining satisfaction with teaching activity through the student body by measuring the actions that are the responsibility of the teacher and the students themselves, as well as whether there are differences in satisfaction according to gender and the university in which they study. The sample consisted of 206 university students (40.6% men and 59.4% women), enrolled in different Spanish universities (38.3% Jaume I University, 34% University of Valencia and 27.7% University of Vigo). Data were collected using the Student Satisfaction Questionnaire (MOCSE-SSPQ). The SPSS 25.00 statistical package was used. Cronbach’s alpha was performed to evaluate the questionnaire, in addition to Pearson’s linear regression analysis, Student’s t-test, one-factor ANOVA and simple linear regression analysis to measure the main objective proposed. The results showed that there is a relationship between satisfaction with the actions carried out by teachers and the actions carried out by students. Little difference was found between the perception that men and women have of the variables measured, although there are significant differences in satisfaction, depending on the university in which the students are enrolled. Finally, the dimensions studied were strong predictors of satisfaction with the teaching activity. It is concluded that the empirical data obtained provide the basis for designing effective teaching projects in university teaching to increase the results of university student satisfaction.